Proses Pengiriman FCL dari CFS ke Container Yard di Pelabuhan MTKI oleh PT Elang Sriwijaya Perkasa - Wamsal Suryady Maruli Tua Sinaga; Yursal Yursal; Taruna Ginting (Port Management and Maritime Administration Journal, 2026)
This study discusses the delivery process of Full Container Load (FCL) from the Container Freight Station (CFS) to the Container Yard (CY) at MTKI Port (Masaji Tatanan Kontainer Indonesia) by the shipping agency (EMKL) PT. Elang Sriwijaya Palembang. This FCL delivery process is a critical stage in the shipping logistics chain as it ensures that containers fully loaded from the stacking warehouse can be placed in the port's stacking yard safely and in accordance with procedures. Shipping documents and administrative completeness are also vital components that must be fulfilled to ensure the container transfer process runs smoothly and complies with Port regulations. The purpose of this research is to identify the stages of the FCL delivery process, the parties involved, the obstacles faced during the container transfer process, and the solutions implemented to overcome them. The results show that the FCL delivery process involves several steps, starting from the issuance of shipping documents, administrative inspection, and coordination with port authorities, to the actual transfer of containers to the CY. Furthermore, obstacles were found in the form of administrative delays, limited loading and unloading equipment, and coordination issues between the EMKL and the port operator. This research is expected to serve as a reference for EMKL companies and related institutions in improving the effectiveness of the FCL delivery process, thereby supporting the smooth flow of goods at the port and enhancing the efficiency of Indonesia's maritime logistics activities. The methods used in preparing this paper are field research and library research methods.